A toxic gain of function variant in MAPK8IP3 provides novel insights into JIP3 cellular roles - Wei Zhang; Swapnil Mittal; Ria Thomas; Anahid Foroughishafiei; Ricardo Nunes Bastos; Wendy K. Chung; Konstantina Skourti-Stathaki; Stanley T. Crooke (JCI Insight, 2025)
Mitogen-activated protein kinase 8 interacting protein 3 (MAPK8IP3/JIP3) is a member of the kinesin family known to play a role in axonal transport of cargo. Mutations in the gene have been linked to severe neurodevelopmental disorders, resulting in developmental delay, intellectual disability, ataxia, tremor, autism, seizures, and visual impairment. A patient who has a missense mutation in the MAPK8IP3 gene (c. 1714 C>T, Arg578Cys) (R578C) manifests dystonia, gross motor delay and developmental delay. Here we show that the mutation is a toxic gain of function mutation which alters the interactome of JIP3, disrupts axonal transport of late endosomes, increases signaling via c-Jun N-terminal kinase (JNK), resulting in apoptosis, and disrupts the dopamine receptor 1 (D1) signaling while not affecting the dopamine receptor 2 (D2) signaling. Further, in the presence of the mutant protein, we show that 80% reduction of mutant JIP3>80% and 60% reduction of wild-type JIP3 by non-allele selective phosphorothioate (PS)-modified antisense oligonucleotides (ASOs) is well tolerated by several types of cells in vitro. Our study identifies several important new roles for JIP3 and provides important insights for therapeutic approaches, including antisense oligonucleotide reduction of JIP3.